Surface roughness analysis on titanium alloy Ti-6AI-4V ELI during turning with uncoated carbide insert - Mastuki, Ammar Aizat (2019)
This research work, focus on the turning of titanium alloy Ti-GAI-4V ELI by using the uncoated carbide insert, Titanium alloy is extensively used in aerospace, medical instruments, steam boiler, and heavy duty products because of their high specific strength (strength-to-weight ratio), which is retained at elevated temperatures, as well as their fracture resistance and exceptional corrosion resistance. However the machinability of titanium and its alloys is generally considered o be poor owing (o several inherent properties of materials. The machining of titanium and its alloys is challenging owing to the elevated mechanical strength and low thermal conductivity of these alloys, which not only induces serious thermomechanical dynamic stress on the cutting instruments but also guarantees that most of the heat produced during cutting remains inside the instrument. In addition, titanium is extremely reactive at typical temperatures produced during machining, with most tool components and coatings further reducing the life of the instrument. These issues seriously affect the productivity of titanium alloys. Due to that, the tool will worn out very fast and hence poor surface finish on material generated. The objectives of this paper is to investigate surface integrity of surface machined material, These experiments are performed under dry condition. There are two significant factors involving surface roughness of alloy tested which are depth of cut and feed rate.